2020
DOI: 10.1002/jcla.23298
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of cyclin D1 can act as an independent prognostic marker for longer survival time in human nasopharyngeal carcinoma

Abstract: Background Cyclin D1 is an essential part of oncogenic transformation. We previously proved that cyclin D1 was upregulated in nasopharyngeal carcinoma (NPC) and promoted the NPC cell proliferation. But the association between cyclin D1 and the clinical outcome of NPC has not yet been determined. The study explores the possible relevance between the cyclin D1 expression and clinical parameters and its predictive value of prognosis in NPC patients. Methods We analyzed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Dysregulated Cyclin D1 is an oncogene and is regarded as a driver of solid tumors [ 40 ]. Previous studies found that Cyclin D1 was significantly upregulated in NPC and positively related to its progression [ 41 , 42 ]. Cyclin D1 can be the downstream regulatory factor of NF-kappaB p65 [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulated Cyclin D1 is an oncogene and is regarded as a driver of solid tumors [ 40 ]. Previous studies found that Cyclin D1 was significantly upregulated in NPC and positively related to its progression [ 41 , 42 ]. Cyclin D1 can be the downstream regulatory factor of NF-kappaB p65 [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of cyclin D1 has been studied for years and is associated with poor prognosis (OR 5.2, CI 95% 2.8-10.2, p = 0.0001) and lymph node metastasis (p = 0.015) (7,8). The increased expression of cyclin D1 is related to the promotion of cell proliferation because it hastens the transition of the G1 phase to the S phase (9).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies found that a high expression of cyclin D1 is associated with good prognosis (14). In contrast, the studies on lung cancer, oropharyngeal cancer, and colorectal cancer suggested that high levels of cyclin D1 related to poor prognosis (8,15).…”
Section: Discussionmentioning
confidence: 99%
“…β-catenin has been found to regulate oncogenes such as CYCLIN D1, PDK, MTC-1, MMP7, fibronectin, COX-2, AXIN-2, and C-MYC. Most of the downstream oncogenes have been related to NPC prognosis [ 18 , 58 , 60 , 61 , 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%